AN ANALYSIS OF STUDENT'S ERROR IN WRITING ABILITY THROUGH DESCRIPTIVE TEXT OF VII GRADE OF SMP N 4 TAKENGON - Muhammad Hasyimsyah Batubara; Delfia Herwanis; Safitriana Safitriana (Jurnal As-Salam, 2021)
The research is interested in analyzing and focusing on students' errors in writing descriptive text such as developing ideas, organizing ideas, grammar, mechanics, and using vocabulary better. This research aims to analyze the errors in writing students of descriptive text in the VII grade of SMP N 4 Takengon. This research used a qualitative method, technique of collecting data by observation, interview, and documentation. Based on the result, the writer concluded:  After researching and analyzing the data, the writer concludes as the kinds of errors in writing students of descriptive text at VII grade of SMP N 4 Takengon are from three aspects they are adjective, conjunction, and present tense. The finding shows the total error of students in writing adjectives, which is 23 students. In the total error of students in writing conjunctions, there were 24 students. The total error of students in writing the present tense, which is 21 students. If it is related to the student's error statement in writing, the value of about 94% and 166.6% total wrong word in error because students' understanding is still low about writing.